Thin-strut bioresorbable-polymer sirolimus-eluting stent use for an optimal result of rescue coronary angioplasty in acute myocardial infarction failed thrombolytic therapy: the Bangladesh National Heart Foundation Annual Conference OCT-assisted live case - Malik, Fazila-Tun-Nesa; Dutta, Ashok; Banik, Dhiman; Shahriar Huq, Tawfiq; Kalimuddin, Muhammad; Mikołajczyk, Filip; Musialek, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
A 47-year-old man, smoker, was transferred to the Department of Cardiology Catheterization Laboratory at the National Heart Foundation (NHF) Hospital & Research Institute [1] in Dhaka, Bangladesh, from a remote hospital after streptokinase failure to reperfuse anterior ST-elevation acute myocardial infarction (STEMI). The patient had presented in a local hospital with a severe retrosternal pain of 6-hour duration (transportation > 2 h). A diagnosis of anterior STEMI was made. The patient received i.v. morphine (8 mg) and intravenous streptokinase (STK, 1.5 million units i.v.) as the first-line reperfusion therapy in most areas of Bangladesh. Other medications were oral aspirin (300 mg), loading dose of generic clopidogrel (300 mg), and high-dose (80 mg) generic atorvastatin, all of which are now manufactured in the country.